Best treatment options for occult breast cancer: A meta-analysis - Wang, Rong; Yang, Hong-xin; Chen, Jie; Huang, Jian-jun; Lv, Qing (Frontiers in Oncology, 2023)
Objectives Occult breast cancer (OBC) is a rare malignant breast tumor. Because of the rare cases and limited clinical experience, a huge therapeutic difference has existed all over the world and standardized treatments have yet been established. Methods A meta-analysis was conducted using MEDLINE and Embase databases to identify the choice of OBC surgical procedures in all studies: (1) patients undergoing axillary lymph node dissection (ALND) or sentinel lymph node biopsy (SLNB) only; (2) patients undergoing ALND with radiotherapy (RT); (3) patients undergoing ALND with breast surgery (BS); (4) patients undergoing ALND with RT and BS; and (5) patients undergoing observation or RT only. The primary endpoints were mortality rates, the second endpoints were distant metastasis and locoregional recurrence. Results Among the 3,476 patients, 493 (14.2%) undergo ALND or SLNB only; 632 (18.2%) undergo ALND with RT; 1483 (42.7%) undergo ALND with BS; 467 (13.4%) undergo ALND RT and BS, and 401 (11.5%) undergo observation or RT only. After comparing the multiple groups, both groups 1 and 3 have higher mortality rates than group 4 (30.7% vs. 18.6%, p < 0.0001; 25.1% vs. 18.6%, p = 0.007), and group 1 has higher mortality rates than groups 2 and 3 (30.7% vs.14.7%, p < 0.00001; 30.7 vs. 19.4%, p < 0.0001). Group (1 + 3) had a prognosis advantage over group 5 (21.4% vs. 31.0%, p < 0.00001). There was no significant difference both in the distant recurrence rates and locoregional rates between group (1 + 3) and group (2 + 4) (21.0% vs. 9.7%, p = 0.06; 12.3% vs. 6.5%, p = 0.26). Conclusion On the basis of this meta-analysis, our study indicates that BS including modified radical mastectomy (MRM) and breast-conserving surgery (BCS) combined RT may appear as the optimal surgical approach in patients with OBC. RT cannot prolong both the time of distant metastasis and the local recurrences.